Alterations of the Gut Microbiome Associated With the Treatment of Hyperuricaemia in Male Rats - Yu, Yiran; Liu, Qiuping; Li, Haichang; Wen, Chengping; He, Zhixing (Frontiers in Microbiology, 2018)
Hyperuricaemia is an important risk factor for many diseases including gout, hypertension, and type II diabetes. The gut microbiota is associated with hyperuricaemia and has also been demonstrated to play significant roles in the effects of drug therapy. This study used Illumina MiSeq sequencing to explore alterations of the gut microbiome associated with allopurinol and benzbromarone treatment in the male rat with hyperuricaemia. After drug treatment, both allopurinol and benzbromarone caused an increase of the genera Bifidobacterium and Collinsella and a decrease of the genera Adlercreutzia and Anaerostipes. In addition, allopurinol and benzbromarone caused respective unique changes in genera. The genera Bilophila, Morganella and Desulfovibrio specifically decreased due to allopurinol treatment. Decreased Butyricimonas and Ruminococcus and increased Proteus were caused by benzbromarone treatment. The PICRUST analysis indicated that allopurinol renovated the disorder of nucleotide metabolism and benzbromarone renovated the disorder of lipid metabolism in the gut microbiota of male rats with hyperuricaemia. These findings demonstrated that the gut microbiota may be altered by the treatment of hyperuricaemia with allopurinol and benzbromarone in male rats. Such alterations of the gut microbiota could be considered as indicators of the effectiveness of drug therapy.